PERILAKU MAHASISWA RANTAU DI PEKANBARU (Studi Kasus Mahasiswa Pelalawan) - Sudirmanto, Susilo; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Research on overseas behavior in pekanbaru (a typical study in pelalawan students). this research was conducted with the aim of explaining how the behavior of overseas students with the new environment and the factors causing the change. in this study the author uses a type of qualitative research which is an attempt to present the social world, and its perspective in life, in terms of concepts, behaviors, perceptions, and problems about the human being examined. Data collection techniques using purposive sampling method, where the subject is determined by the researcher himself, where the informants used by Pelalawan students from HIMAWAN, amounting to 10 people. the technique of concluding data uses observation, interview and documentation techniques. the results of the study prove that indeed there is a change in some behavior of overseas students such as: how to dress, hairstyles, learning activities, ways of speaking and so on, but students make these changes for the good and progress of themselves. this is influenced by several factors such as: playmates and living environment (campus).Â Keywords: Behavior, Change,Â  Pelalawan Students